2014
DOI: 10.1016/j.cmet.2014.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Peptide Induces Mitochondrial Dysfunction by Inhibition of Preprotein Maturation

Abstract: Most mitochondrial proteins possess N-terminal presequences that are required for targeting and import into the organelle. Upon import, presequences are cleaved off by matrix processing peptidases and subsequently degraded by the peptidasome Cym1/PreP, which also degrades Amyloid-beta peptides (Aβ). Here we find that impaired turnover of presequence peptides results in feedback inhibition of presequence processing enzymes. Moreover, Aβ inhibits degradation of presequence peptides by PreP, resulting in accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
199
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(206 citation statements)
references
References 32 publications
3
199
1
3
Order By: Relevance
“…Interestingly, two enhancers (stock numbers 23714 and 24137) cover the same gene CG3731, whose protein product is a homolog of the mammalian peptidase (mitochondrial processing) beta (PMPCB). The inhibition of its processing of the presequences of mitochondrial proteins was proposed to be a general mechanism for diverse Aβ-induced mitochondrial dysfunctions [12] . Nevertheless, it should be pointed out that the genetic backgrounds of the deficient lines might differ from each other, and from wild-type and Aβ arc flies, so further experiments are needed to validate these suppressors and enhancers.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, two enhancers (stock numbers 23714 and 24137) cover the same gene CG3731, whose protein product is a homolog of the mammalian peptidase (mitochondrial processing) beta (PMPCB). The inhibition of its processing of the presequences of mitochondrial proteins was proposed to be a general mechanism for diverse Aβ-induced mitochondrial dysfunctions [12] . Nevertheless, it should be pointed out that the genetic backgrounds of the deficient lines might differ from each other, and from wild-type and Aβ arc flies, so further experiments are needed to validate these suppressors and enhancers.…”
Section: Resultsmentioning
confidence: 99%
“…To distinguish if this is a special characteristic of these particular non-processed proteins or a general feature of mas1 mitochondria we chose the control proteins Hsp10, which is not processed upon import into the mitochondrial matrix, and Mrpl32, that is processed by the m-AAA protease but not by MPP. 15,37 Both, Hsp10 and…”
Section: Non-permissive Temperaturementioning
confidence: 99%
“…Deletion of proteases in different organisms for in vivo analysis or purified proteases incubated with cell lysates allowed specific substrate identification of an individual protease 5,15,42,45. However, the in vivo analysis of essential proteases was not feasible so far due to the lack of a model system possessing a specifically impaired protease activity.…”
mentioning
confidence: 99%
“…Nevertheless, recent studies suggest that the oligomers of the Aβ peptide are more toxic than their monomeric and fibrillary aggregates and although the molecular mechanisms that lead to the disease are not well understand, sufficient evidence regarding the role of oxidative stress and mitochondrial dysfunction in AD are recognized as early events in the development of the disease [32]. It has been shown that Aβ peptide gains access into mitochondrial matrix and its progressively accumulates mediates mitochondrial stress by interfering with enzyme activity, affecting the neural bioenergetics, an important pathway in the pathogenesis of this devastating disease [33,34].…”
Section: IImentioning
confidence: 99%